2017
DOI: 10.1161/circgenetics.117.001778
|View full text |Cite
|
Sign up to set email alerts
|

New Blood Pressure–Associated Loci Identified in Meta-Analyses of 475 000 Individuals

Abstract: Background Genome-wide association studies have recently identified over 400 loci that harbor DNA sequence variants that influence blood pressure (BP). Our earlier work identified and validated 56 single nucleotide variants (SNVs) associated with BP from meta-analyses of Exome Chip genotype data. An additional 100 variants yielded suggestive evidence of association. Methods and Results Here, we augment the sample with 140,886 European individuals from the UK Biobank, in whom 77 of the 100 suggestive SNVs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 47 publications
(80 reference statements)
0
36
0
Order By: Relevance
“…We demonstrated that mice expressing human Nox5 in a podocyte‐specific manner exhibit podocyte injury and renal dysfunction,28 and that human Nox5 expression in mesangial cells causes renal fibrosis, nephropathy, and exacerbated atherosclerosis in diabetic mice 29. Findings from recent genome wide‐association studies of 475 000 individuals identified Nox5 as a candidate blood pressure–associated gene 30. Together, these data suggest an important (patho)physiological role for Nox5 in the cardiovascular system.…”
mentioning
confidence: 70%
“…We demonstrated that mice expressing human Nox5 in a podocyte‐specific manner exhibit podocyte injury and renal dysfunction,28 and that human Nox5 expression in mesangial cells causes renal fibrosis, nephropathy, and exacerbated atherosclerosis in diabetic mice 29. Findings from recent genome wide‐association studies of 475 000 individuals identified Nox5 as a candidate blood pressure–associated gene 30. Together, these data suggest an important (patho)physiological role for Nox5 in the cardiovascular system.…”
mentioning
confidence: 70%
“…76 More recently, genome-wide association study data from more than 450,000 individuals identified Nox4 and Nox5 as novel blood pressureerelated genes. 77 Although oxidative stress is likely not the sole cause of hypertension, it amplifies blood pressure elevation in the presence of other prohypertensive factors, such as Ang II, ET-1, aldosterone, and salt.…”
Section: Evidence Supporting a Role For Ros And Oxidative Stress In Hmentioning
confidence: 99%
“…Over the past decade, GWAS have led to the identification of thousands of genetic loci robustly associated with a wide range of diseases and traits , including >500 genetic loci associated with adiposity traits , mainly with BMI (as a proxy of overall obesity) and waist‐to‐hip ratio (WHR; proxy of fat distribution) , but also with more refined adiposity traits, such as body fat percentage (BF%) , circulating leptin levels , specific fat depots, such as visceral and subcutaneous adipose tissue (VAT, SAT) , and extreme and early‐onset obesity . In addition, GWAS have also identified hundreds of loci associated with cardiometabolic traits, including glycemic traits , circulating lipid levels , blood pressure , coronary artery disease (CAD) and type 2 diabetes .…”
Section: Using Human Genetics To Identify New Pathways and Mechanismsmentioning
confidence: 99%